The effect of transformational leadership on job satisfaction the mediating role of knowledge management and organizational culture in adnoc refining company in UAE - Salem Ibrahim Mohamed, Alhammadi Mahmoud (2023)
Today, transformational leadership is considered the most influential leadership style for modern organizations. To boost job satisfaction in the oil and gas industry, the interrelated roles of transformational leadership, knowledge management, and organizational culture help companies achieve this goal. ADNOC has initiated plans to enhance the capabilities of its workforce and develop their performance, but until the present, it is unknown to what extent this plan is successful. As transformational leadership promotes the needs of employees without exemptions, the ambiguity surrounding organization culture and knowledge management may hinder the efforts of those leaders to boost affective and cognitive job satisfaction. Thus, the aim of this study is to examine the mediating roles of organizational culture and knowledge management in the relationship between transformational leadership and job satisfaction. In addition, proposing a framework that interrelates these variables in the energy sector To achieve this goal, a quantitative methodology was used, and a simple random technique was adopted for distributing the questionnaires to a sample of 450 employees working at ADNOC Refining Company. The result showed that knowledge management and organizational culture have partial mediating effects on the association between transformational leadership and job satisfaction. This study makes several theoretical and practical contributions to the topic of leadership and organizational theories, such as validating a scale for measuring the dimensions of job satisfaction in the O&G industry and providing empirical evidence on the significant role of transformational leaders in ADNOC. It is recommended that leaders in this company promote knowledge production, knowledge integration, and knowledge utilization to establish an organizational culture that is based on employee orientation, customer focus, and responsibility. All these factors contribute to affective, cognitive, and behavioral job satisfaction.